Retribusi Pengelolaan Sampah Dalam Menakar Kesiapan Diet Sampah Plastik Warga Batam - Adi Irawan Setiyanto; Riri Zelmiyanti; Arif Darmawan (Politeknik Negeri Batam, 2021)
One of the regional revenues comes from regional levies, the total regional fees for the city of Batam in 2018 amounted to 94,581,392,967.00 while in 2019 it decreased to 90,511,150,389.64 (Batam City RAPBD Report). The garbage retribution collected for the Batam community ranges from Rp. 7,000 to Rp. 50,000 depending on the building area, the rules for the cost of waste retribution are regulated in the Batam City Garbage Regional Regulation. One of the levies is used for waste management. When viewed from the budget provided by the Batam city government through the Environmental Service (DLH) of 97 billion for waste management in Batam during 2017. This study aims to see the behavior of the Batam community in waste management and the readiness of Batam citizens in implementing a plastic waste diet. The method used in this research is descriptive analysis by observing and distributing questionnaires. The practical benefits that are wanted after conducting research to encourage people to reduce the amount of waste production and are useful for policy makers in evaluating policies that have been implemented. The waste produced by the community is around 0.5 kg to 7 kg per day. From the data obtained, 74% of Batam people use waste management services. As many as 209 respondents or 52.3% of the people of Batam understand the term plastic diet, almost half of the people do not know about the plastic diet. 92.8% of Batam people know about the dangers of plastic waste for the environment, so it takes maximum effort so that people know how to reduce plastic use. The main problems in waste management stem from: waste taken by officers is not sorted, lack of counseling from waste managers. 98% of respondents are willing to reduce plastic waste, therefore the government must continue to socialize ways to reduce plastic use.